Konstruksi Keadilan Gender Dalam Wacana dan Praktik Poligami - Kholisah, Nur; Jannah, Nurul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research is motivated by the structural inequalities and systematic impacts of polygamy in Indonesia, which often ignores the principle of gender justice. Although legally restricted by the Marriage Law and the Compilation of Islamic Law, requirements such as